PERANCANGAN APLIKASI SISTEM INFORMASI PENJUALAN RUMAH BERBASIS MOBILE WEB DENGAN METODE STRING MATCHING ( STUDI KASUS: BUANA PROPERTI) - Imelda Sri Dumayanti; Posma SM Lumbanraja; Sabrina Ginting (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Buana Property is one of the developers in the housing sector or is engaged in the business of selling, buying, and renting property. Advances in technology make Buana properties that always want to grow and be better known in the community with the construction of a mobile commerce system. So far, the system at Buana Properti is still a physical store that is offline so it is not well known to the public, there is no housing sales information system that uses a mobile web system. Therefore, this system is needed to simplify the process of selling housing at Buana Properti Medan which makes it easier for buyers to make house purchases at Buana Property. The system built will also provide a home search feature where this search feature is built using the String Matching method with the Knuth-Morris Pratt (KMP) model. The system that has been built itself uses HTML and PHP programming languages ​​in building mobile web and MySQL as a place database storage. The results of this study are that this system can assist buyers in finding homes that match their wishes and make purchase and payment transactions more easily.